Pola Komunikasi J- Art Gallery Medan Dalam Memasarkan Produk Kerajinan Tangan Dari Limbah Koran Bekas - Zahwa, Dara Dinda; Yenni, Elvita (Universitas Muhammadiyah Sumatera Utara, 2024)
Communication pattern refers to a form or model of relationship between two or more people in the process of sending and receiving messages in a certain way. This study aims to determine the communication patterns used by J-Art Medan Gallery in marketing handicraft products made from used newspaper waste. The formulation in this study is the communication patterns used by the owner of J-Art Medan Gallery in marketing handicraft products from used newspaper waste so as to attract a lot of consumer attention. In this study researchers used descriptive methods with a qualitative approach with data collection techniques through observation, interviews, and documentation. The results showed that there are three communication patterns used by J-Art owners in marketing their products, namely primary, secondary, and circular communication patterns. Primary communication patterns occur directly or indirectly between gallery owners and consumers. Secondary communication patterns occur through social media, J-Art owners use platforms such as Facebook and Instagram to promote products with high consistency and interaction. Circular communication patterns are reflected through consumer feedback received through the comments column on social media posts that create ongoing interactions between gallery owners and consumers.